A novel multi-epitope mRNA vaccine against colorectal cancer: in silico design and immune efficacy profiling - Wang, Lin; Zhou, Xiaofei; Wei, Yu; Lin, Jianping (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) has emerged as a growing global health challenge, while immunotherapy, particularly mRNA-based cancer vaccines, has emerged as a promising approach due to its ability to induce targeted immune responses with minimal systemic toxicity. This study aimed to design a multi-epitope mRNA vaccine targeting tumor-specific antigens (TSAs) as a cancer therapeutic regimen.ResultsWe chose six CRC-specific TSAs and selected their appropriate epitopes with immunoinformatic tools. In order to enhance the vaccine stability, we subsequently optimized the open reading frame (ORF) sequences, which demonstrated the highest structural stability among all evaluated approaches. Furthermore, we built a CNN model combined with RNA large language model (RNA-FM) embeddings to screen 212 candidate 5’UTR sequences and identify variants that boost the vaccine’s translational efficiency. Finally, in silico immune simulations confirmed the vaccine’s ability to elicit robust humoral and cellular immune responses.ConclusionThis study presents an in silico designed mRNA vaccine against colorectal cancer (CRC). Immune simulations demonstrated that this mRNA vaccine can elicit strong antitumor immune responses, indicating it is an effective and promising candidate that warrants further in vitro and in vivo investigations. Additionally, this work highlights the potential of in silico approaches in vaccine design and provides valuable insights for the development of effective vaccines targeting CRC.